Structural performance envelopes in load space. (January 2021) - Dharmasaroja, A.; Armstrong, C.G.; Murphy, A.; Robinson, T.T.; Iorga, N.L.; Barron, J.R.
ABSTRACT: Visualising the loads that a structure can tolerate provides a key insight into the structural design process, especially for materials and structures that are governed by complex failure criteria. This paper proposes a general method for efficient construction of performance envelopes in load space, and demonstrates the approach with two examples. The performance envelope identifies all possible failure modes, all the redundant and non-redundant structural constraints, and the limiting failure mode in a particular direction in load space. Once the envelope has been constructed, the structural reserve factors can be calculated extremely quickly. In design such envelopes are most useful for structural analysis processes which involve a very large number of load cases, and where the cost of constructing an envelope for a given feature is relatively modest.